A study about drummer preference on traditional and matched stick grip toward professional and student of music school majoring in drum / Mohd Faizat Ahmad Zabidi - Ahmad Zabidi, Mohd Faizat (2011)
A number of new intakes for universities are increasing every year and this also experienced by UiTM Faculty of MUSIC. From my observation here, fresh student In this faculty always face a problem {0 find their basic fundamental on their technique or Virtuoso usually for student majoring In drums they always have a problem to find the right technique that they should learn firs‘ and develop their abilities to be a drummer One of the problems Is that In terms of the right techniques that appropriate to grip a stick. There is two basic style of holding a grip which is traditional grip and matched grip. Beginner‘s student always has a problem to play which grip first. This study is conducted to give a clear understanding for beginner's drummer and to give them the right technique to hold the stick for purpose of starting me learning lesson to be a good drummer thus (0 be one of the best drummer in Malaysia. This study is conducted in UiTM Shah Alam Faculty of Music and interview session with the professional who are the drum lecturer and also to a student who majoring m drum. They are the best person that can give their view and share their experience because they have gone through the situation and already master the technique The first technique that relates to the study is Traditional grip which also known as Orthodox grip It is a technique used to hold drum sticks while playing percussion Traditional grip IS almost exclusively used to play the snare drum, especially the marching snare drum, and often We drum kit The overhand grip most commonly used Is the American grip With ‘he underhand grip, there are several different techniques employed which Involve slight variations in finger positioning and usage.